The pacing strategy and technique of male cross-country skiers with different levels of performance during a 15-km classical race - Welde, B.; Stöggl, T. L.; Mathisen, G. E.; Supej, M.; Zoppirolli, C.; Winther, A. K.; Pellegrini, B.; Holmberg, H. C. (PLOS ONE, 2017)
In this study the pacing strategy, cycle characteristics and choice of technique of elite male cross-country (XC) skiers during a three-lap, 15-km classical race with interval start were measured. During the Norwegian Championships in 2016, fast (n = 18, age: 26±4 yr; height: 182±4 cm; body mass: 78±3 kg (means±SD)) and slow skiers (n = 18, age: 22±2 yr; height: 183±5 cm; body mass: 78±6 kg) were video recorded on flat (0°), intermediate (3.5°) and uphill sections (7.1°) of the first and final laps. All skiers adopted a positive pacing strategy, skiing more slowly (11.8%) with shorter cycles (11.7%) on the final than first lap (both p<0.001; p 2 = 0.93 and 0.87, respectively). The fast skiers were 7.0% faster overall (p<0.001, d = 4.20), and 6.1% (p<0.001, d = 3.32) and 7.0% (p<0.001, d = 3.68) faster on the first and final laps, respectively, compared to slower skiers. On all sections of both laps, the fast skiers exhibited 9.5% more rapid (p 2 = 0.74) and 8.9% (p 2 = 0.48) longer cycles (both p<0.001). On intermediate terrain, the fast skiers employed primarily double poling (DP, 38.9% on the first lap) and double poling with a kick (DPKICK, 50% on the final lap). In contrast, the slow skiers utilized for the most part DP alone (lap 1: 33.3%, lap 3: 38.9%) or in combination with other techniques (lap 1: 33.3%, lap 3: 38.9%) and decreased their usage of DPKICK from 27.8% on the first to 16.7% on the final lap. Skiing velocity on flat and intermediate terrain proved to be the best predictor of race performance (p<0.001). In conclusion, during a 15-km classical XC skiing race, velocity and cycle length decreased from the first to the final lap, most extensively on flat terrain and least uphill. Moreover, on the intermediate sections the fast and slow skiers chose to use different techniques.